Amino acid transporter SLC7A11/xCT at the crossroads of regulating redox homeostasis and nutrient dependency of cancer - Pranavi Koppula; Yilei Zhang; Li Zhuang; Boyi Gan (Cancer Communications, 2018)
Abstract Cancer cells often upregulate nutrient transporters to fulfill their increased biosynthetic and bioenergetic needs, and to maintain redox homeostasis. One nutrient transporter frequently overexpressed in human cancers is the cystine/glutamate antiporter solute carrier family 7 member 11 (SLC7A11; also known as xCT). SLC7A11 promotes cystine uptake and glutathione biosynthesis, resulting in protection from oxidative stress and ferroptotic cell death. Recent studies have unexpectedly revealed that SLC7A11 also plays critical roles in glutamine metabolism and regulates the glucose and glutamine dependency of cancer cells. This review discusses the roles of SLC7A11 in regulating the antioxidant response and nutrient dependency of cancer cells, explores our current understanding of SLC7A11 regulation in cancer metabolism, and highlights key open questions for future studies in this emerging research area. A deeper understanding of SLC7A11 in cancer metabolism may identify new therapeutic opportunities to target this important amino acid transporter for cancer treatment.